Languages and Compilers for Parallel Computing 22nd International Workshop, LCPC 2009, Newark, DE, USA, October 8-10, 2009, Revised Selected Papers - Gao, Guang R.; Pollock, Lori L.; Cavazos, John.; Li, Xiaoming; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-workshop proceedings of the 22nd International Workshop on Languages and Compilers for Parallel Computing, LCPC 2009, held in Newark, DE, USA, in October 2009. The 25 revised full papers and 5 revised short papers presented were carefully reviewed and selected from 52 submissions. The papers address all aspects of languages, compiler techniques, run-time environments, and compiler-related performance evaluation for parallel and high-performance computing and extend the area of interest to new parallel computing accelerators such as IBM Cell processor and Graphic Processing Unit (GPU) presenting the latest work of leading researchers and practitioners in the field.
A Communication Framework for Fault-Tolerant Parallel Execution -- The STAPL pList -- Hardware Support for OpenMP Collective Operations -- Loop Transformation Recipes for Code Generation and Auto-Tuning -- MIMD Interpretation on a GPU -- TL-DAE: Thread-Level Decoupled Access/Execution for OpenMP on the Cyclops-64 Many-Core Processor -- Mapping Streaming Languages to General Purpose Processors through Vectorization -- A Balanced Approach to Application Performance Tuning -- Automatically Tuning Parallel and Parallelized Programs -- DFT Performance Prediction in FFTW -- Safe and Familiar Multi-core Programming by Means of a Hybrid Functional and Imperative Language -- Hierarchical Place Trees: A Portable Abstraction for Task Parallelism and Data Movement -- OSCAR API for Real-Time Low-Power Multicores and Its Performance on Multicores and SMP Servers -- Programming with Intervals -- Adaptive and Speculative Memory Consistency Support for Multi-core Architectures with On-Chip Local Memories -- Synchronization-Free Automatic Parallelization: Beyond Affine Iteration-Space Slicing -- Automatic Data Distribution for Improving Data Locality on the Cell BE Architecture -- Automatic Restructuring of Linked Data Structures -- Using the Meeting Graph Framework to Minimise Kernel Loop Unrolling for Scheduled Loops -- Efficient Tiled Loop Generation: D-Tiling -- Effective Source-to-Source Outlining to Support Whole Program Empirical Optimization -- Speculative Optimizations for Parallel Programs on Multicores -- Fastpath Speculative Parallelization -- PSnAP: Accurate Synthetic Address Streams through Memory Profiles -- Enforcing Textual Alignment of Collectives Using Dynamic Checks -- A Code Generation Approach for Auto-Vectorization in the Spade Compiler -- Portable Just-in-Time Specialization of Dynamically Typed Scripting Languages -- Reducing Training Time in a One-Shot Machine Learning-Based Compiler -- Optimizing Local Memory Allocation and Assignment through a Decoupled Approach -- Unrolling Loops Containing Task Parallelism.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Electronic data processing; Computer Science; Programming Languages, Compilers, Interpreters; Programming Techniques; Data Structures; Computing Methodologies; Models and Principles; Computer Communication Networks